Legitimidade democrática da jurisdição constitucional: contribuições da discussão entre procedimentalismo e substancialismo à práxis judiciária brasileira - Fonseca, João Lucas (2019)
"All power emanates from the people." From this fundamental proposition, starting point of the Brazilian Constitution which reminds us of the duty to fill any political power exercise with a democratic background, the present study is going to be developed, examining the reason to the democratic legitimacy of constitutional jurisdiction exercise by the judicial branch. The problematic can be summed up in one question: from where does the legitimacy reason that authorizes constitutional judges, holders of non-elegible offices, to give the last ruling in constitutional matters, a very important document to the democratic regime, come? Considering this, to the optimal construction of the stated reasoning, the main conditions of the problematic and the reasons why it has followed the constitutional jurisdiction in all its history are going to be explored. Afterwards, starting from the proceduralist and substantialist theorys a answer to the main problem will be sought. Utilizing a summary of the addressed positions, a central conclusion will be reached: constitutional jurisdicton‘s democratic legitimacy comes from the protection of the essential fundamental rights to democracy‘s well being. Confronting said proposition with Brazilian historical reality, a second conclusion will be reached: that Brazilian constitutional justice‘s democratic legitimacy, a late modernity country, must be aligned with a compatible procedure to constitution‘s ruling character, committed to the modernity promises layed in its text. However, the defense of this procedure, as it‘s going to be seen at the end of the study, doesn‘t implie adherence to a judicial voluntarism, a weakener of law‘s autonomy and authority, wich the jurisdiction must be absolutely against.